IMPACT OF THE JAKARTA – SURABAYA HIGH – SPEED TRAIN ON PASSENGERS OF THE JAKARTA – SURABAYA EXECUTIVE TRAIN CORRIDOR - Utomo, Djoko Prijo; Lestari, Prasetyaning Diah Rizky; Sucipto, Sucipto; Nurhidayat, Asep Yayat (BPPT, 2020)
Due to the increasing demand for travel by train in recent years, the large potential number of passengers in Jakarta - Surabaya corridor needs to be anticipated with adequate transportation system planning so that the bottlenecks on available transportation network system can be minimized. This paper analyses the potential competition between the demand of executive passenger train and Jakarta-Surabaya high-speed train which will be built by the Government as planned. This study only use travel time variables and ticket rates as independent variables between executive passenger train and high-speed train, then stated preference methods and binomial logit models are used as tools for processing data. As a result, we believe that the operation of Jakarta-Surabaya high-speed train will have a negative impact on the demand of executive passenger train on this route.